2015
DOI: 10.1111/jcpe.12422
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine expression in peri‐implant crevicular fluid in relation to bacterial presence

Abstract: Profuse bleeding and/or suppuration in untreated peri-implantitis can be associated with higher concentrations of IL-1β, IL-8, TNF-α and VEGF in peri-implant crevicular fluid. A higher concentration of IL-1β in peri-implant crevicular fluid was found in samples that were positive for E. coli or S. epidermidis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 19 publications
2
30
0
Order By: Relevance
“…Thus, the initial search provided 26 full‐text publications, which were comprehensively evaluated. Of these 26 papers, nine studies were excluded because they did not match the inclusion/exclusion criteria or had unclear information (Table ). Seventeen studies were then included, based on the electronic search and one study was subsequently included based on the manual search.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the initial search provided 26 full‐text publications, which were comprehensively evaluated. Of these 26 papers, nine studies were excluded because they did not match the inclusion/exclusion criteria or had unclear information (Table ). Seventeen studies were then included, based on the electronic search and one study was subsequently included based on the manual search.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies showed higher levels of IL-1β in PICF than healthy implant sites [7,21,22,30,35,36,41-47]. Of the 10 studies assessed TNF-α, 3 of them showed no relationship with this cytokine with peri-implant inflammation [7,25,43], while other 7 studies showed significant relationship with this cytokine [23,24,36,41,46-48]. These findings suggest that pro-inflammatory cytokines such as IL-1β and TNF-α are up to date, the most promising proteins to be used as markers in PICF for differentiation between peri-implantitis and healthy implants.…”
Section: Discussionmentioning
confidence: 99%
“…In as much as PIP involves a robust host response to a substantial oral bacterial burden, with an imbalance between pro‐ and anti‐inflammatory responses and tissue destruction of the periodontium (soft and hard tissue damage), analysis of cytokine levels representing these responses in peri‐implant crevicular fluid (PICF) could assist in identifying early biological responses that might presage disease. Biomarkers linked to PIP include an array of pro‐inflammatory cytokines (tumor necrosis factor‐α, interferon‐γ, interleukin (IL)‐1β, IL‐6, anti‐inflammatory cytokines (IL‐4 and IL‐10), chemokines (IL‐8, monocyte chemoattractant protein (MCP)‐1 and macrophage inflammatory protein (MIP‐1α), and tissue destructive enzymes (matrix metalloproteinases (MMP‐8) . Of these, pro‐inflammatory cytokines demonstrate the strongest association with PIP .…”
Section: Introductionmentioning
confidence: 99%